(untitled) (Bangladesh Journal of Medical Science, 2010)
Loeshe in 1976 propounded the ‘Specific Plaque Hypothesis’ and efforts have been done since, to formulate a periodontal treatment regimen based on targeting of specific microorganisms. Antibiotics have gained importance as an arsenal in the treatment of periodontitis. This review takes a concise view on the role of antibiotics in periodontics. This review puts importance of antibiotics in a nutshell as a quick reference for the general practitioners in treating periodontal diseases. The selection and indication for the use of antibiotics is given with a note on resistance Key words: Periodontitis; antibiotics. DOI: 10.3329/bjms.v8i4.4706 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp91-101